e-Learning: Kesiapan Teknis Civitas Akademika dan Pemilihan e-Media dalam Transformasi Menuju Sistem Pengajaran Elektronik - Budi Sutedjo Dharma Oetomo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
In order to fulfill the goal of Indonesia development especially in spreading theeducation to all citizen in Indonesia, government and private business develope a newlearning system which called e-Learning. e-Learning is a way to use Internet technology ineducation.Research found that the problem of implementation is not only appears in computerinstallation, networking and its connection, but also in user technical readiness. Researchalso found that the successfull e-Learning will be depend on the choosen e-Media.Keywords: e-learning, pengajaran elektronik, e-media.